2020
DOI: 10.1111/all.14704
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of safety and efficacy of belimumab in treating immune‐mediated disorders

Abstract: Background Biologic agents (also termed biologics or biologicals) are becoming increasingly important in the treatment of immune‐mediated diseases. However, the diversity of clinical trials along with the fast pace of publication makes it difficult to determine the level of evidence for the use of a biologic for a given disorder. To address this challenge, we are publishing a series of systematic reviews evaluating the safety and efficacy of B cell–targeting biologics for the treatment of immune‐mediated disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…31 Moreover, BAFF blockade therapy such as belimumab has shown prominent therapeutic effect in systemic lupus erythematosus and other autoimmune diseases such as rheumatic arthritis and sjögren's syndrome. 32 , 33 , 34 , 35 Therefore, multicentre and large‐scale trails are anticipated to investigate the therapeutic application of belimumab in ITP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Moreover, BAFF blockade therapy such as belimumab has shown prominent therapeutic effect in systemic lupus erythematosus and other autoimmune diseases such as rheumatic arthritis and sjögren's syndrome. 32 , 33 , 34 , 35 Therefore, multicentre and large‐scale trails are anticipated to investigate the therapeutic application of belimumab in ITP.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective phase IIb trial in ITP reported notable efficacy and safety of a combined rituximab and belimumab regimen in persistent or chronic adults ITP patients, for that 80% patients achieved an overall response without serious complications after 5 weeks of treatment 31 . Moreover, BAFF blockade therapy such as belimumab has shown prominent therapeutic effect in systemic lupus erythematosus and other autoimmune diseases such as rheumatic arthritis and sjögren's syndrome 32–35 . Therefore, multicentre and large‐scale trails are anticipated to investigate the therapeutic application of belimumab in ITP.…”
Section: Discussionmentioning
confidence: 99%
“…As established in our previous studies (11)(12)(13)(14), we included randomized controlled trials (RCTs), their extension trials and their substudies with predefined endpoints. If there were no RCTs, we included prospective case series including at least three patients and non-randomized clinical studies with at least five patients per intervention group.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Belimumab ist ein humanisierter monoklonaler Antikörper gegen das Zytokin BAFF, der zur Behandlung von systemischem Lupus erythematosus (SLE) zugelassen ist [190]. Eine doppelblinde, placebokontrollierte Studie zur Untersuchung der Wirksamkeit und Sicherheit von Belimumab bei Patienten mit IIM, die in der Vorgeschichte unzureichend auf eine 3-monatige Behandlung mit Glukokortikoiden und/oder einem anderen Immunsuppressivum angesprochen haben, wird derzeit durchgeführt (ClinicalTrials.gov-Kennung: NCT02347891).…”
Section: Pharmakologische Wirkstoffe Die Auf B-zellen Den Interferon-...unclassified